Predictors of Unintended Pregnancy and Sexual Reproductive Health Conditions in Survivors of Violence - Al-Aitan, Sarah Ahmad Majed; Samawi , Osama Suleiman; Aqel, Ibrahim Said; Al-Salem, Hussein Mohammad; Banat, Hassan Mohammad; Al-Etan, Saad Ahmad (Tropical Health and Medical Research, 2023)
The effect of violence on women's sexual reproductive health is of significant importance; this study aimed to study the association between gender-based violence with unintended pregnancy and common sexual reproductive health conditions. The size of the study sample was 102, who were survivors of violence. Direct interviews collected the data, and the researchers used a structured 30-question questionnaire. Results showed that early marriage was significantly associated with unintended pregnancy. The mean of unintended pregnancy for the marriage age group <=18 years was 1.79, which is higher than the mean of the>18 years marriage age group. The t-value is 2.616, and the significance value is 0.010, meaning there are statistically significant differences in unintended pregnancy in favour of the age group <=18 years. Results also indicated the prevalence of unmet needs for contraception in the study sample was 55% among survivors. 26% of women received inadequate antenatal visits primarily due to financial reasons, and almost half (47%) of births were delivered by the Cesarian section; the most popular method is IUD. In conclusion, gender-based violence is a consistent and strong risk factor for unintended pregnancy, especially in the child marriage age group, so it's necessary to overlook sexual reproductive health among survivors of violence as it might be threatened.